Revision of Labidostomis (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini) with large united elytral spot from Iran and adjacent countries - Bezděk, Jan (Zootaxa, 2018)
The Labidostomis Chevrolat, 1936 species with large united metallic spot on elytra from Iran and adjacent countries are revised. Six species, all belonging to nominate subgenus, are recognized: L. elegans Lefèvre, 1876 (Caucasus, Turkey, Iran), L. kantneri Warchałowski, 2004 (Iran), L. limbata (Lacordaire, 1848) (Israel, Syria), L. luristanica Warchałowski, 2004 (Iran), L. shirazica Lopatin, 1979 (Iran), and L. regalini sp. nov. (Turkey). Colour photos of male habitus, mandibles and internal sclerites of aedeagus, as well as drawings of male and female genitalia are provided. Internal sclerites of aedeagus are used for species identification.